KEBERADAAN ASAS PACTA SUNT SERVANDA DAN GOOD FAITH MENURUT HUKUM INTERNASIONAL DAN HUKUM ISLAM - Iffan, Ahmad (JOURNAL EQUITABLE, 2018)
The principle of pacta sunt servanda and good faith (good faith) is the basic norms and principles in carrying out international relations carried out between countries and international organizations. This principle is also an important element in implementing international agreements and also being an amplifier so that the agreement must be carried out by the parties to the agreement. The above principle also contains sanctions and consequences if one party breaks the contents of the agreement. So modern western European civilization grew above Islamic civilization. Therefore, the understanding and provisions of Islam cannot be separated from the material and international understanding with various provisions, ranging from organizations, relations between countries to international agreements. Islam highly upholds the agreement and does its best, this can be seen. Never mentioned in the long history of the Muslims, especially in the golden days of Islam that they fell in treason against the agreement that was held with the non-Muslims. Compliance and seriousness in implementing agreements for Muslims is not just a form of agreement, but this will also involve the faith and character of a Muslim in keeping his promises, therefore the principle of pacta sunt servanda and good faith is a principle that is upheld by Muslims even though it is mentioned by different mentions and sentences